Analisis Aktiyitas Tax Avoidance Dari Perspektif Moral - Setiadi Alim Lim (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2021)
Tax avoidance and tax evasion are not new problems for many countries in the world. They are not unique phenomenon in modern tax problems since many years. Many researchers state that tax avoidance has grown significantly in recent decades. It has been continuously eroded the integrity of the tax base in many countries. Tax avoidance and tax evasion have the same goal: to minimize or to eliminate tax liability. Tax avoidance is legal activity, whereas tax evasion is illegal activity. Although tax avoidance is not formally violate the tax law, but it is usually in contradiction with the intent and spirit of the tax law. This paper is aimed to determine whether tax avoidance is moral or not.